Physical properties and fustal biomass of Pinus engelmannii from a plantation in Durango - Goche-Télles, José Rodolfo; Carrillo-Parra, Artemio; Razo-Zarate, Ramón; Rodríguez-Laguna, Rodrigo; Palacios-Mendoza, Celina (Ecosistemas y Recursos Agropecuarios, 2023)
Commercial forest plantations are a strategy to protect natural  forests from overexploitation, so it is important, to know the physical properties of the wood from these plantations. The objective of the work was to determine the quality of the wood based on its physical properties and wood biomass from a Pinusengelmannii plantation of 17 years. The normal diameter and total height were measured in all the trees found in 20 rectangular sites of 3.0 x 6.0 m distributed in four lines. At each site, with a Pressler drill, a growth core was taken at 1.30 m high, in two dominant trees. Physical properties, basic density (DB), moisture content (MC), total volumetric shrinkage (TVC), and fiber saturation point (FSP) were determined by applying the typical formulas. The biomass was estimated with the values of volume and basic density, in addition to three allometric equations. The results were: BD = 0.379 g cm−3 , MC = 199.37%, SVT = 13.63%, FSP = 39.28% and an average stem biomass of 22.79 kg. The ANOVA showed that the section within the tree had a significant influence (p < 0.05) on BD and MC, with a high negative correlation (r = - 0.96). The plantation wood turned out to be homogeneous with respect to BD, MC, and SVT, while the first two variables showed radial variation. The biomass showed a close relationship with the basic density and the normal diameter.